Beyond patient delay, navigating structural health system barriers to timely care and treatment in a high burden TB setting in Papua New Guinea. Issue 1 (2nd January 2023) - Jops, Paula; Cowan, John; Kupul, Martha; Trumb, Richard Nake; Graham, Stephen M.; Bauri, Mathias; Nindil, Herolyn; Bell, Stephen; Keam, Tess; Majumdar, Suman; Pomat, William; Marais, Ben; et al.
ABSTRACT: Tuberculosis (TB) is a major public health issue in Papua New Guinea, with incidence rates particularly high in the South Fly District of Western Province. We present three case studies, along with additional vignettes, that were derived from interviews and focus groups carried out between July 2019 and July 2020 of people living in rural areas of the remote South Fly District depicting their challenges accessing timely TB diagnosis and care; most services within the district are only offered offshore on Daru Island. The findings detail that rather than 'patient delay' attributed to poor health seeking behaviours and inadequate knowledge of TB symptoms, many people were actively trying to navigate structural barriers hindering access to and utilisation of limited local TB services. The findings highlight a fragile and fragmented health system, a lack of attention given to primary health services, and undue financial burdens placed on people living in rural and remote areas associated with costly transportation to access functioning health services. We conclude that a person-centred and effective decentralised model of TB care as outlined in health policies is imperative for equitable access to essential health care services in Papua New Guinea.